Murder on Bank Street : a gaslight mystery - Thompson, Victoria (Victoria E.) (Thompson, Victoria (Victoria E.). Gaslight mystery., 2008)
Malloy takes up the unsolved murder of Dr. Brandt, but the shocking revelations he uncovers may destroy Sarah-- and Malloy's hope for any future with her.